Mechanisms of Investigation Criminal Planning Involving Children as Performer - Andrian Subarjo; Umar Ma'ruf (Law Development Journal, 2021)
The objectives of this research are as follows: To identify and analyze the process of resolving the crime of premeditated murder which involves a child as the perpetrator. To find out and analyze legal considerations by the police in law enforcement against the crime of accidental murder involving a child as the perpetrator. The research method used is research that combines juridical and empirical. Based on the results of this study, the process of resolving premeditated murder involving children as perpetrators is required for the settlement of cases of juvenile crime as regulated in Article 7 paragraph (1) of Act No. 11 of 2012 concerning the Juvenile Criminal Justice System.